Kritik Karl Marx terhadap Konsep Buruh Kapitalis Kajian Komparatif Ekonomi Syariah atas Buku Das Kapital I - Qomar, Moh. Nurul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Comparative study of Karl Marx's economic thinking about labor becomes an effort to prove theoretically that there are differences in the concept of Karl Marx's workers with the Islamic economic system both in basic and implication. The results of the study stated that a. work according to the socialist and Islamic economics is a way to meet the needs of human life (prosperity and welfare), it's just the concept of Karl Marx based on materialism whereas according to Islamic economics in addition to meeting the needs of life also has a spiritual dimension (worship). b. workers as owners of labor must have more value on the results of their production. This can happen with the role of the State in production without class. Islam allows the use of labor with a contract of ijaˆrah in which there are rules and conditions for employers and workers.